[Students on hillside] - Frank Aston::::::photographer::: (1907)
Students on hillside, possibly the hill behind the campus, possibly propagating grapes. Probably 1907-08 school year, with professor of botany and horticulture Ira Judson Condit standing. Likely to also include Jagat Bondhu Dev, Jogadish C Goswami, and Devendra N Guha, three students from India who were enrolled in a one-year special study program in agriculture in the 1907-08 school year.